2019
DOI: 10.1097/jcn.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

“Why Would I Choose Death?”

Abstract: Background Although cardiology organizations recommend early introduction of palliative care for patients with heart failure (HF), integration has remained challenging, particularly in patients with cardiac devices such as cardiac implantable electronic devices and left ventricular assist devices. Study authors suggest that patients often have limited and erroneous understanding of these devices and their implications for future care. Objective The aim of this study was to assess perceptions of cardiac devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…20,21 In addition, a systematic review of quantitative studies on ACP in patients with HF indicated that ACP intervention methods are highly heterogeneous. 22 Although the experience of patients with HF is reported to be unique, 6,18 ACP interventions specific to patients with HF remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…20,21 In addition, a systematic review of quantitative studies on ACP in patients with HF indicated that ACP intervention methods are highly heterogeneous. 22 Although the experience of patients with HF is reported to be unique, 6,18 ACP interventions specific to patients with HF remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HF do not tend to consider their own mortality, as the characteristics of the disease follow an uncertain course. A previous study showed that patients focus on their persistent physical symptoms and do not consider the end-of-life stages of their condition 6. In addition, advances in therapeutic agents and treatments specific to HF, such as implantable devices, promote patient optimism and delay their participation in end-of-life discussions 6.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations